PENGARUH DAYA MICROWAVE TERHADAP RENDEMEN MINYAK KAYU MANIS (Cinnamomum burmannii) DENGAN METODE MICROWAVE HYDRODISTILLATION - Hananta, Bagas Oktaihza; Pratama, Putra; Aswan, Arizal; ., Fatria; ., Zurohaina (KINETIKA, 2020)
Cinnamon oil is usually obtained by conventional methods and takes a long time. One of the newer methods that can be used is microwave hydrodistillation. The advantage of microwaves is their ability to provide energy directly to all ingredients, which saves time compared to conventional methods. This study aims to study the effect of time and microwave power on the yield of essential oils obtained. The solvent used was aquadest, the variables tested in the study were the raw material for leaves and cinnamon bark weighing 150 grams and 100 grams, respectively. The microwave power used is 180, 360, 450 Watt. The operating conditions in this method are at atmospheric pressure. When using 180W power, the yield of leaf oil and cinnamon bark is 0.65% and 0.51%, at 360W power is 0.96% and 0.75%, and 450W power is 0.88% and 0.89%. %. The value of specific energy consumption (SEC) at 180W microwave power is 1.78 kWh / gr and 3.40 kWh / gr, at 360W power is 1.50 kWh / gr and 2.91 kWh / gr and 450W power is 1.80 kWh / gr and 2.72 kWh / gr.